2020
DOI: 10.1111/pbi.13490
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas‐based precision genome editing via microhomology‐mediated end joining

Abstract: Summary Gene editing and/or allele introgression with absolute precision and control appear to be the ultimate goals of genetic engineering. Precision genome editing in plants has been developed through various approaches, including oligonucleotide‐directed mutagenesis (ODM), base editing, prime editing and especially homologous recombination (HR)‐based gene targeting. With the advent of CRISPR/Cas for the targeted generation of DNA breaks (single‐stranded breaks (SSBs) or double‐stranded breaks (DSBs)), a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…Error-prone NHEJ is designed for gene knockout by disrupting the coding sequence of that target gene due to the introduction of random indels or frameshift mutations while HDR and HR repairs are programmable and their effects are predictable. A more precise error-prone repair mechanism alternative to HR, microhomology-mediated end joining (MHEJ), has been believed to enhance the efficiency of genome editing in plants [ 38 ]. The mechanism of TALEN-based genome-editing is basically via the disruption of the effector-binding element of the S gene promoter which eventually impairs the compatible molecular interactions between the effector and the target S gene.…”
Section: Genome-editing: Mechanisms and Variant Toolsmentioning
confidence: 99%
“…Error-prone NHEJ is designed for gene knockout by disrupting the coding sequence of that target gene due to the introduction of random indels or frameshift mutations while HDR and HR repairs are programmable and their effects are predictable. A more precise error-prone repair mechanism alternative to HR, microhomology-mediated end joining (MHEJ), has been believed to enhance the efficiency of genome editing in plants [ 38 ]. The mechanism of TALEN-based genome-editing is basically via the disruption of the effector-binding element of the S gene promoter which eventually impairs the compatible molecular interactions between the effector and the target S gene.…”
Section: Genome-editing: Mechanisms and Variant Toolsmentioning
confidence: 99%
“…The mutant efficiency of MMEJ is similar to the NHEJ mechanism, which show a high potential for precise gene editing compared with HDR ( Seol et al, 2018 ). Yao and co-workers showed that the mutation frequencies were as high as 20% by using MMEJ-mediated knock-in, which was approximately 10-fold higher than the HDR-based approach ( Van Vu et al, 2021 ).…”
Section: The Mechanism Of Crispr-cas9 Systemmentioning
confidence: 99%
“…These editors have the distinct advantage of inducing simultaneous mutations at C > T and A > G target sites under the guidance of a single sgRNA. Moreover, the saturation degree and the diversity of mutation types of the target gene were increased significantly using this technology [103][104][105][106][107][108].…”
Section: Double Base Editing Techniquesmentioning
confidence: 99%